1993
DOI: 10.1093/intimm/5.3.311
|View full text |Cite
|
Sign up to set email alerts
|

CD28 mAbs with distinct binding properties differ in their ability to induce T cell activation: analysis of early and late activation events

Abstract: A panel of eight different CD28 mAbs was used to analyse the structure-function relationships of the CD28 molecule. The results of binding inhibition experiments show a complex and heterogeneous pattern of inhibition; however a subgroup of mAbs was identified, namely CD28.1, CD28.3, and CD28.5, which exhibited almost identical inhibition profiles. To test the hypothesis that the different binding specificities are related to functionally distinct subregions of the CD28 molecule, the ability of each mAb to (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…Myeloma cells were activated by the CD28.2 anti-CD28 mAb known to activate T cell CD28 molecules. 12 This was further confirmed in the experiments shown in Figure 4. Indeed, allogenic T cells were poorly stimulated by irradiated XG-6 myeloma cells.…”
Section: Lack Of Obvious Biological Effects Of Cd28 Activation In Myesupporting
confidence: 68%
See 2 more Smart Citations
“…Myeloma cells were activated by the CD28.2 anti-CD28 mAb known to activate T cell CD28 molecules. 12 This was further confirmed in the experiments shown in Figure 4. Indeed, allogenic T cells were poorly stimulated by irradiated XG-6 myeloma cells.…”
Section: Lack Of Obvious Biological Effects Of Cd28 Activation In Myesupporting
confidence: 68%
“…Our previous studies have shown that IL-6 was a growth factor for myeloma cells 18 and that IL-6-dependent myeloma cell lines could be reproducibly obtained from patients with terminal disease. 10 By using the agonist CD28.2 mAb (known to activate T cells) in combination with TPA, 12 we found no modulation of the proliferation of the IL-6-dependent XG-1 and XG-6 HMCL or of the autonomously growing RPMI8226 and U266 HMCL. This is in agreement with a lack of modulation by the anti-CD28 mAbs of IL-6R and gp130 IL-6 transducer expression on myeloma cells or of IL-6 production by myeloma cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Antibodies-Anti-human CD28 monoclonal antibodies (mAbs) 248, CD28.2, and CD28.6 and anti-human CD3 mAb 289 have already been described (40). The anti-Itk, anti-Tec, anti-p62 dok rabbit polyclonal antisera were raised against murine Itk, Tec, and p62 dok proteins using synthetic peptides corresponding to amino acid residues 605-625 (DRP-PFSQLLSQLAEIAEAGL), amino acid residues 162-179 (EIKKRRPP-PPIPPEEENT), and amino acid residues 424 -437 (PQGLILPESGT-TRGS), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs from healthy donors were stained with 5 mL of the following mouse anti-human mAbs per million of cells: ECDconjugated anti-CD3, PC5-conjugated anti-CD14, PC5-conjugated anti-CD19 (to select CD3 have been previously incubated with CD3 mAb (clone OKT3) plus CD28 mAb (clone CD28.2) [23] or isotypic control (IgG1). Anti-CD3 and anti-CD28 mAbs were used at 0.3 mg/mL and 10 mg/mL, respectively.…”
Section: Expression Profile Of Cd277 On T-cell Subpopulationsmentioning
confidence: 99%